Incidence of gonorrhoea diagnosed in GUM clinics in South Thames (west) region. Issue 5 (1st October 1999) - Hickman, M; Judd, A; Maguire, H; Hay, P; Charlett, A; Catchpole, M; Nayagam, A; Renton, A
Abstract : OBJECTIVES: To describe the incidence of gonorrhoea diagnosed in genitourinary medicine (GUM) clinics in South Thames (West) between 1995 and 1996, and how it changed among population subgroups. SETTINGS AND SUBJECTS: Cases of uncomplicated and complicated gonorrhoea diagnosed at 13 GUM clinics in the former South Thames West (STW) Regional Health Authority that reported disaggregate data to the South Thames GUM Clinic Collaborative STD Surveillance Scheme. METHODS: Annual incidence rates (per 100, 000) of gonorrhoea diagnoses by sex, age group, ethnic group, area of residence, and year were calculated. Poisson regression models were used to calculate risk ratios (RR) to describe the key differences in the variation of gonorrhoea cases by these variables. Relative differences in the incidence of diagnosed gonorrhoea between 1995 and 1996 were investigated by including an interaction between year and the other variables (age group, sex, ethnic group, region) and testing whether any were significant using a likelihood ratio test. RESULTS: Area of residence, sex, age group, and ethnic group were key predictors of the rates of diagnosed gonorrhoea. The risk ratio for gonorrhoea (after adjustment for the other variables) was: 13 times higher among blacks than the white population; twice as high in inner London compared with outer London; and three times lower in the "shire" region compared with outer London. The rate of diagnosed gonorrhoea was significantly higher in the black population in the shire region than the inner London white population. The rate of gonorrhoea diagnosed by GUM clinics from 1995 to 1996 almost doubled in the white population aged 15-44 years, from 16 cases per 100, 000 to 30 cases per 100, 000 (adjusted RR 2.0, 95% CI 1.6 to 2.4), whereas increased rates in the black and Asian/other ethnic groups were not statistically significant (adjusted RR 1.1, 95% CI 0.9 to 1.4; and 1.4, 95% CI 0.7 to 2.7 respectively). CONCLUSION: The observed increase in gonorrhoea between 1995 and 1996 occurred mostly among heterosexual white men and women. Overall, the rates of gonorrhoea among young people, especially in the black population and in inner London represent a significant public health problem that may merit further targeted interventions, the effectiveness of which could be monitored through further development of routine surveillance data.